2021
DOI: 10.1038/s41598-021-01455-4
|View full text |Cite
|
Sign up to set email alerts
|

Local, multimodal intralesional therapy renders distant brain metastases susceptible to PD-L1 blockade in a preclinical model of triple-negative breast cancer

Abstract: Despite recent progress in therapeutic strategies, prognosis of metastatic triple-negative breast cancer (TNBC) remains dismal. Evidence suggests that the induction and activation of tumor-residing conventional type-1 dendritic cells (cDC1s) is critical for the generation of CD8+ T cells that mediate the regression of mammary tumors and potentiate anti-PD-1/PD-L1 therapeutic efficacy. However, it remains unknown whether this strategy is effective against metastatic TNBC, which is poorly responsive to immunothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Additionally, increasing radiotherapy treatments to three and performing surgery only one day after poly(I:C)/aCD40 treatment both independently enhanced survival in mice bearing orthotopic 4T1-luc tumors ( 120 ). Prior studies with this ISIM treatment in the primary treatment setting demonstrated that it increased frequencies of activated, effector CD4+ and CD8+ T cells in AT-3 murine tumors ( 114 ) and decreased PMN-MSDCs in AT-3 and 4T1 BC murine tumors ( 115 ).…”
Section: Preclinical Studiesmentioning
confidence: 98%
“…Additionally, increasing radiotherapy treatments to three and performing surgery only one day after poly(I:C)/aCD40 treatment both independently enhanced survival in mice bearing orthotopic 4T1-luc tumors ( 120 ). Prior studies with this ISIM treatment in the primary treatment setting demonstrated that it increased frequencies of activated, effector CD4+ and CD8+ T cells in AT-3 murine tumors ( 114 ) and decreased PMN-MSDCs in AT-3 and 4T1 BC murine tumors ( 115 ).…”
Section: Preclinical Studiesmentioning
confidence: 98%
“…The model consisted in the tumor inoculation in mammary fat pad and intracardiac injection of AT-3 cells (a primary mammary gland carcinoma of a transgenic mice). The findings were that in situ induction and activation of dendritic cells (cDC1s) by intratumoral injection of FMS-related tyrosine kinase 3 ligand (FLT3-L), mammary tumor irradiation and injection of toll-like receptor 3 (TLR3)/ CD40 at the peritumoral site leads into the infiltration of CD8þ T cells in distant nonirradiated central nervous system lesions [11]. Importantly, this treatment initiates systemic antitumor immunity, delays the progression of established TNBC BM, and renders them responsive to anti-PDL1 therapy to improve survival [11].…”
Section: Intracardiac Injectionmentioning
confidence: 99%
“…The findings were that in situ induction and activation of dendritic cells (cDC1s) by intratumoral injection of FMS-related tyrosine kinase 3 ligand (FLT3-L), mammary tumor irradiation and injection of toll-like receptor 3 (TLR3)/ CD40 at the peritumoral site leads into the infiltration of CD8þ T cells in distant nonirradiated central nervous system lesions [11]. Importantly, this treatment initiates systemic antitumor immunity, delays the progression of established TNBC BM, and renders them responsive to anti-PDL1 therapy to improve survival [11]. Another preclinical BCBM mouse model has been used to test the combination of doxorubicin, a chemotherapy drug that induces between other effects senescence, with anti-PD1 to improve the efficacy of immunotherapy.…”
Section: Intracardiac Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food and Drug Administraion (FDA) has approved a number of ISV-based cancer immunotherapies, such as Bacilus Calmette-Guerin (BCG) for in situ vaccination, toll-like receptor agonists for in situ vaccination, oncolytic virus for in situ vaccination, and in situ vaccination with cytokines and immune checkpoint blockade. ISV involves manipulation of intratumoral immune cells by injecting immunomodulators ( 89 ) and local ablative therapies which are used to release tumor antigens from the therapy-killed tumor cells ( 90 ). Besides, local treatment with vaccines and adjuvant is another option to provoke immune system in situ ( 91 ).…”
Section: Vaccine Delivery Platformsmentioning
confidence: 99%